New data on the distribution of the ragweed leaf beetle Zygogramma suturalis (Fabricius, 1775) and the olive-shaded bird-dropping moth Acontia candefacta (Hübner, (1831) in the Kharkiv region - Lezhenina, I.; Vasylieva, Yu.; Liudvinskyi , V. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. Clarification of the distribution of the ragweed leaf beetle — Zygogramma suturalis (Fabricius, 1775) (Coleoptera: Chrysomelidae) and the olive-shaded bird-dropping moth — Acontia candefacta (Hübner, 1831) (Lepidoptera: Noctuidae) in the Kharkiv region. Methods. The material was collected within five villages of Lozova district, located in the south of Kharkiv region. The main method of collection was the use of the insect net, in addition, the route method was used to record olive-shaded bird-dropping moth. Results. The ragweed leaf beetle — Zygogramma suturalis (Fabricius, 1775) and olive-shaded bird-dropping moth — Acontia candefacta (Hübner, 1831) were found on Ambrosia artemisiifolia L. from June to August 2024. This is the first time for the Lozova district that we have recorded these species there. The olive-shaded bird-dropping moth was found in large numbers on the ragweed plants in August, in some places the number reached 40 butterflies per 100 m of the route, and 31 specimens of caterpillars per 50 sweeps of the net. The second generation of Acontia candefacta was on the plants in the flowering phase. At the same time, single caterpillars were found in the ragweed locations in the Kharkiv district, which is located in the northern part of the region. The ragweed leaf beetle occurred singly, only three larvae and one beetle were found during the research period. Conclusions. Our findings of Zygogramma suturalis in the Lozova district are the second indication for the Kharkiv region. The results of our research confirm the move of the ragweed leaf beetle to the north, today the Kharkiv region is the northern border of the distribution of the species in Ukraine. The olive-shaded bird-dropping moth is also expanding its area to the north of the Kharkiv region, where it becomes numerous in some places. The ragweed leaf beetle is rare, so it does not affect the condition of ragweed in Kharkiv region in any way, the olive-shaded bird-dropping moth, despite the high number of the second generation, also does not control it, because at that time the plants are very developed. Our photo materials are added to iNaturalist and UkrBin databases.